Statistical Learning Impairments as a Consequence of Stroke - Shaqiri, Albulena; Danckert, James; Burnett, Lauren; Anderson, Britt (Frontiers in Human Neuroscience, 2018)
Statistical learning is a skill necessary for successful rehabilitation after a stroke, as most rehabilitation techniques rely on retraining and relearning potentially lost functions. In order to examine how brain injury affects the ability to learn and update statistical representations, we had participants with left and right brain injuries perform an auditory statistical learning task. Participants listened to two languages with made-up words that were defined by the transition probability between syllables. Following the passive listening, learning was assessed with a two-alternative forced choice test. As in previous studies, we found that controls have a capacity limitation for statistical learning, as they learned the second language less well than the first. But most importantly, we found that brain damaged patients showed impaired statistical learning. This impairment could not be explained by language or cognitive deficits. As statistical learning is a critical skill for daily life and for post-stroke rehabilitation, a better appreciation of the nature of this impairment will improve the evaluation of rehabilitation procedures.